THE RIGHT TO REPAIR: A PERSPECTIVE FROM CONSUMER PROTECTION LAW IN INDONESIA - Ahmad Fachri Faqi; Fadilla Jamila; Nur Khadijah (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
Obstacles to independent repair make the right-to-repair movement grows around the world. The method in this research is normative legal research, which is carried out by library research on the right of repair concept analyzed based on consumer protection law in Indonesia, in addition to conducting a comparative study of the development of the the-right-repair movement in the United States and the European Union to understand the right to repair concept comprehensively. The result shows that several right-to-repair legislative products have been introduced in the United States and the European Union. Consumer protection law in Indonesia based on Law 08/1999 does not expressly stipulate the right to repair as consumers' rights in Indonesia. Consumer protection law in Indonesia is arguably not in consumers' favor since it still allows manufacturers to impose a measure preventing consumers from completing repairs independently.